Nucleolar Phosphoprotein NPM1 Interacts With Porcine Circovirus Type 3 Cap Protein and Facilitates Viral Replication - Song, Jiangwei; Hou, Lei; Wang, Dan; Wei, Li; Zhu, Shanshan; Wang, Jing; Quan, Rong; Jiang, Haijun; Shi, Ruihan; Liu, Jue (Frontiers in Microbiology, 2021)
Porcine circovirus type 3 (PCV3) is a recently discovered virus with potentially significant implications on the global swine industry. PCV3 replication involves the entry of the viral capsid (Cap) protein with nucleolar localization signals into the nucleus. Using liquid chromatography-mass spectrometry analysis, nucleolar phosphoprotein NPM1 was identified as one of the cellular proteins bound to PCV3 Cap. Co-immunoprecipitation demonstrated that PCV3 Cap interacts directly with NPM1, where the region binding with NPM1 is mapped to amino acid residues 1-38 of Cap. Upon co-transfection, the expression of Cap protein promoted the redistribution of NPM1, which translocated from the nucleus to the cytoplasm and colocalized with Cap in cultured PK15 cells. NPM1 expression was upregulated and translocated from the nucleus to the cytoplasm in PCV3-infected cells, upon siRNA-mediated depletion, or upon treatment with NPM1 inhibitor in PK15 cells with impaired PCV3 replication, as evidenced by decreased levels of viral DNA synthesis and protein expression. By contrast, the replication of PCV3 was enhanced in stably NPM1-expressing cells via a lentivirus-delivered system. Taken together, these findings indicate that NPM1 interacts with PCV3 Cap and plays a crucial role in PCV3 replication.